2020
DOI: 10.3390/nano10091773
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Arsenic (III and V) Removal in Anoxic Environments by Hierarchically Structured Citrate/FeCO3 Nanocomposites

Abstract: Novel citrate/FeCO3 nanocomposites (CF-NCs) were synthesized for effective arsenic (III and V) sorption with constant addition of Fe2+ into HCO3− solution in the presence of citrate. This paper is the first report on the formation of CF-NCs, and in this study we investigate the mechanisms of arsenic uptake by the sorbent under anoxic conditions through various solid- and liquid-phase spectroscopic methods, including X-ray absorption spectroscopy. In CF-NCs, citrate was found to be incorporated into the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…In addition, the amount of citric acid incorporated increased steadily from 0.23 to 0.65 wt % as the carboxylic acid concentration in the synthetic solution increased from 0.1 to 1.0 mM, but malic acid reached a maximum at 0.19 wt %. These results can support the XRD and TEM/SAED results, which showed a disorder in the lattice structure of carbonate mineral upon the incorporation of citric and malic acids [34]. Therefore, it is suggested that only the two carboxylic acids can be favorably incorporated into aragonite, and this tendency is stronger in citric acid than malic acid.…”
Section: Hplcsupporting
confidence: 83%
See 4 more Smart Citations
“…In addition, the amount of citric acid incorporated increased steadily from 0.23 to 0.65 wt % as the carboxylic acid concentration in the synthetic solution increased from 0.1 to 1.0 mM, but malic acid reached a maximum at 0.19 wt %. These results can support the XRD and TEM/SAED results, which showed a disorder in the lattice structure of carbonate mineral upon the incorporation of citric and malic acids [34]. Therefore, it is suggested that only the two carboxylic acids can be favorably incorporated into aragonite, and this tendency is stronger in citric acid than malic acid.…”
Section: Hplcsupporting
confidence: 83%
“…This means that some of the deprotonated carboxylic acids can exist in the form of Ca-organic ligand complexes (i.e., chelate). According to the previous studies, the metal chelate complex species such as (Ca-citrate) − can be strongly involved in its incorporation into carbonate minerals such as calcite or siderite [33,34,52]. Therefore, we deduced that the Ca-organic ligand complexes have an important role in the incorporation of carboxylic acids into aragonite.…”
Section: Theoretical Speciation Modelingmentioning
confidence: 78%
See 3 more Smart Citations